Food security and nutrition implications of intrahousehold bias: a review of literature - Haddad, Lawrence J.; Peña, Christine; Nishida, Chizuru; Quisumbing, Agnes R.; Slack, A. (International Food Policy Research Institute, 1996)
The success of development policy depends on the ability to successfully anticipate the response of individuals to changing incentives. Often, however, actual responses differ from anticipated responses. One important reason for this divergence is a poor understanding of how rights, responsibilities, and resources are allocated within institutions such as the household. The insights derived from intrahousehold research between the late 1970s and the mid-1980s on the determinants of food and nutritional status served as an important catalyst for the general development of the intrahousehold approach to development policy analysis. Despite serving as a building block for the wider study of intrahousehold resource allocation, there has not been an in-depth review of sex and gender differences in the food consumption and nutrition literature in the past 10 years. This paper seeks to fill this gap. In addition, the paper undertakes a review of the gender and poverty literature, because economic access to food is so fundamental to food security and nutrition. Specifically, the paper aims to (1) critically review the existing literature and studies on the distribution of food and other proximate factors within the household (with an emphasis on boy-girl differences), (2) critically review the existing literature and studies in the areas of poverty and gender, gender and income earning, drawing out implications for food and nutrition programs, and (3) highlight some important methodological concerns related to poverty, income, and food consumption measurement.